Professional Language Training of International Students in the Multicultural Environment of University for International Relations - T. Glebova (Vestnik MGIMO-Universiteta, 2014)
The article addresses the specific features of professional language training of international students in the multicultural environment of a Russian university teaching students of international relations. After a brief historical survey of teaching foreign students in the universities of Russia, the writer considers the factors that influence the choice of universities graduating specialists in international relations by foreign students. The author goes on to analyze the specifics of linguisticand socio-cultural environment in Russian universities and its impact on international students stressing the fact that the educational environment at MGIMO-University is multilingual and multicultural. That explains the relevance of studying the quality of professional language training of foreign students in the sphere of international relations. The language of teaching in most universities of the Russian Federation is Russian, besides, all MGIMO students are obliged to learn English either as their first or second foreign language, that is why international students have to study in a tri-lingual environment and the interfering influence of several cultures. The writer points out that under such circumstances it is necessary for future IR specialists to build a number of professionally relevant competences: linguistic, socio-cultural, communicative, and suggests educational technologies that have proved to be effective in building them: case-study, role-plays, etc. The article gives special attention to the place and role of translation in teaching English as translation is a system of encoding within the system of two language systems. Translating phrases from Russian into English the student does 'inner', mental translation using the mother tongue. That makes the author suggest using the students'mother tongues in the teaching process. While learning foreign languages, international students should, along with language material, study the system of values of a different country thus preparing themselves for cross-cultural communication in the professional international community.